Stochastic quantization of real-time thermal field theory - de Aguiar, T. C.; Svaiter, N. F.; Menezes, G. [UNESP] (American Institute of Physics (AIP), 2010)
We use the stochastic quantization method to obtain the free scalar propagator of a finite temperature field theory formulated in the Minkowski space-time. First, we use the Markovian stochastic quantization approach to present the two-point function of the theory. Second, we assume a Langevin equation with a memory kernel and a colored noise. The convergence of the Markovian and non-Markovian stochastic processes in the asymptotic limit of the fictitious time is obtained. Our formalism can be the starting point to discuss systems at finite temperature out of equilibrium. (C) 2010 American Institute of Physics. [doi:10.1063/1.3492927]